The use of vibrational spectroscopy to predict vitamin C in Kakadu plum powders (Terminalia ferdinandiana Exell, Combretaceae). (2nd December 2020) - Cozzolino, Daniel; Phan, Anh Dao Thi; Netzel, Michael E; Smyth, Heather; Sultanbawa, Yasmina
Abstract: BACKGROUND: The objective of this study was to evaluate the feasibility of using either mid‐infrared (MIR) or near‐infrared (NIR) spectroscopy to predict the vitamin C content in Kakadu plum ( Terminalia ferdinandiana Exell, Combretaceae) powder samples. Vitamin C is the main and quality‐determining bioactive compound in Kakadu plum (KP). Kakadu plum powder samples were analyzed by ultra‐performance liquid chromatography coupled to a photodiode array detector (UPLC‐PDA) and scanned using both MIR and NIR spectroscopy. RESULTS: The coefficient of determination (R 2 ) and the standard error in cross validation (SECV) for vitamin C were 0.93 and 1811 mg 100 g dry weight (DW) and 0.91 and 1839 mg 100 g DW using MIR and NIR spectroscopy, respectively. The coefficient of correlation and the standard error of prediction (SEP) obtained using the independent set (n = 5) were 0.65 (SEP: 2367 mg 100 g DW) and 0.73 (SEP: 4773 mg 100 g DW) using MIR and NIR spectroscopy, respectively. CONCLUSIONS: The results obtained in this study clearly showed that it is possible to calibrate IR spectroscopic instruments for the measurement of vitamin C in KP plum powder samples. Mid‐infrared spectroscopy showed the most promising results; however, Fourier transform near‐infrared (FTNIR) spectroscopy also produced models capable of good quantification of this important bioactive compound and vitamin. These findings are promising in terms of using high‐throughput IR spectroscopy as a routine technology to determine vitamin C in plant‐based foods and derived products. © 2020 Society of Chemical Industry